TAX ADMINISTRATION AND THE PRINCIPLE OF “SOLVE ET REPETE” - Trujillo Meza, Julio César (2014)
The subject of taxation is always controversial, since playing two basic elements: the tax creditor and the taxpayer who as a result of an economic transaction and implementation of the event giving rise to the duty, establish a legal relationship of substantial income tax liability and / or formal.The principles for in the tax environment are constitu-tional and non-constitutional principles and specific principles you determine obligations within them the principle of “estoppel” as a common principle in terms of “SOLVE ET REPETE”. This principle applies in both contentious and non-contentious tax processes. The application of this principle leads to the taxpayer have to pay a tax debt against a claimable value is an Order of Determination, a Resolution of Payment Order or Fine Resolution and even having reason the taxpayer should pay a certain sum money to exercise their right to defense and to oppose in the adminis-trative proceedings before the SUNAT, and even the judiciary, including the Constitutional Court. We believe that the National Tax System requires struc-tural changes within and revision of certain principles as would be the subject of this article.